Recycling of Bamboo (Bambusa vulgaris Schrad) recovered from scaffold into material for furniture production (2013)
"Interest is growing daily on the utilization of bamboo as a reliable supplement to wood in furniture production to mitigate the scarcity of wood raw material supply. This study explored the viability of recycling bamboo recovered from scaffold into intermediate raw material for indoor furniture production. Strips were processed from the recovered Bambusa vulgaris Schrad and were subjected to conventional treatment methods with some modification to simplify the treatment. The durability of the treated strip was evaluated in accordance with ASTM D2017. A storage shelf was designed and fabricated using laminates made from the bamboo strips. The diameter and wall thickness of the recovered bamboo culms ranges from 6.00cm -10.00cm and 10.00mm- 12.70mm respectively. The result shows that ordinary soaking of the strips in water for 3 weeks could make the strips to be sufficiently resistant to termite attack but fairly resistant to powder post beetle. Application of kerosene as a secondary treatment will make the resistance of the bamboo strip effective to powder post beetle. A Complete-Knock-Down (CDK) Magazine shelf suitable for office use was fabricated using road side carpentry workshop tools. This study was able to recycle Bambusa vulgaris recovered from scaffolding material into suitable raw material input for the manufacturing of indoor furniture."